Kiester Comfort: Chair Preferences as Observed in a Rheumatology Practice - Rothschild, Bruce; Woods, Robert J. (International Journal of Orthopedics and Rehabilitation, 2021)
Objective: This study was performed to determine why patients preferred either a standard height or a modified taller chair, when asked to sit and stand. Design: One hundred consecutive patients presenting to a rheumatology practice were asked to sit and subsequently arise from chairs of standard 18-inch and 22-inch seat heights. Chair preference and rationale were assessed against demographic, anthropometric and rheumatology diagnostic variations (osteoarthritis and inflammatory arthritis, soft tissue disorders and inflammation, etc.). Results: Both groups (shorter and taller) preferred the conventional height chair, but preference was more prevalent in individuals with shorter limbs. Osteoporosis was the only statistically significant sign/disease factor associated with chair height choice. Among the 61 who preferred the shorter conventional chair, 13 did so because it was easier from which to arise, 17 reported that it was simply “more comfortable,” while 30 reported that they preferred that their feet touch the floor. Conclusion: Assessment of the rationale for patient chair height preference must consider both factors of comfort and ease of standing. Some aspects of chair design can address patient comfort, while others address reducing joint loads and range of motion. Personal preference for chair height should be factored into social interactions.